Postcolonial reading of select poems of A.K.Ramanujan - Sivalingam, Maaran (Journal of English Language and Literature (ISSN: 2368-2132), 2020)
The proposed paper will attempt at making a close scrutiny of A.K.Ramanujan’s poems ‘Snakes’, ‘A poem on particulars’, and ‘Small-scale reflections on a great house’, in the light of postcolonialism . Though many attempts have already been made at highlighting postcolonial and postmodern traits, in many Indian poems in English, they have not fore grounded the points of deviation, while applying these theories to Indian poems written in English. The present paper will take up the use of the English language and projection of macrocosmic self (nation) through the microcosmic self (family) for analysis and demonstrate how A.K.Ramanujan’s poems mentioned above can be seen as exemplifying them in clear-cut as well as concrete terms. Besides showing the scope for interpreting these three poems from this perspective, the proposed paper also argues that it is the interplay of binary opposites such as the colonizer and the colonized in terms of handling the form and individual self and the collective self in terms of the content that makes possible the postcolonial reading of these three poems.